Assessment of Heavy Metal Concentrations in Sediment, Water and Fish from the Ankobra and Tano River Basins in Ghana - Awuah, G.K. (University of Ghana, 2016)
Background: Arsenic (As), mercury (Hg) and lead (Pb) are toxic heavy metals that occur naturally in the environment. However, their levels are on the rise due to anthropogenic activities posing threat to aquatic wildlife and humans. Objectives: The aim of the study was to assess As, Hg and Pb concentrations in sediment, water and fishes from the Ankobra and Tano River in the Western Region of Ghana, where human activities; especially the artisanal gold mining have been suspected of grossly polluting the drainage systems. Methods: An analytical cross-sectional study was conducted to determine the concentration of As, Hg and Pb in fish and aquatic media (water and sediment) from the Tano and Ankobra River basins of Jaway Wharf – Ellenda and Sanwoma respectively. As, Hg and Pb levels in the tissues (muscles) of different fish species “Ekpoke” Ctenopoma kingsleyae, “Ekpoke” Sarotherodon galilaues, “Ekpoke” Sarotherodon melanotheron, “Adwene” Clarias gariepinus, “Nzerma” Pomadasys jubelini, “ Bile” Parachanna obscura, and “Senzeke” Parapenaeus longirostris (n=53), water samples (n=30) and sediment samples (n=25) were measured using the Atomic Absorption Spectrophotometer (AAS) Pinnacle 900T (Perkin Elmer, USA). Statistical analysis was done using Microsoft version 10 excel spread sheet and STATA software version 13 (StataCorps LP, Chicago, USA). Results: Heavy metal concentration was in the order; Hg>As>Pb across the study sites. Overall, the mean concentrations of Hg and As were highest in fish (2.09 ± 1.29 mg/Kg) and (2.80 ± 1.52 mg/Kg), followed by sediment (1.40 ± 1.78 mg/Kg) and (0.61 ± 0.40 mg/Kg), and water (0.09 ± 0.36 mg/L) and (0.06 ± 0.05mg/L) respectively. Pb levels were highest in sediment (1.46 ± 4.26 mg/Kg), f the variability of overall HM levels in sediment, water and fish were not significantly different (p=0.828, 0.570 and 0.978 respectively). Generally, there were no significant differences in all the levels of As, Hg and Pb in water, sediment and fish in both Ankobra and Tano Rivers. Conclusion: As and Hg levels in both Tano and Ankobra were above the WHO recommended levels for pristine freshwater ecosystems and may therefore pose a threat to aquatic wildlife and human health. ollowed by water (0.14 ± 0.10 mg/L), and then fish (0.11 ± 0.11 mg/Kg) respectively. However,
Thesis(MSc)-University of Ghana, 2016
Keywords: Heavy Metal Concentrations; Sediment; River Basins